Abduction of Anglican Church Envoy Terry Waite in Lebanon 1987 – 1991: A Study in British Documents - Dr. Karim Ahmed Hami Al-Saadoun (Journal of College of Education, 2026)
The kidnapping of Anglican Church representative Terry White, a key negotiator in the foreign hostage crisis in Lebanon (the American kidnappers) in particular, was a great shock to the international community and a disappointment to those waiting for a solution to the hostage crisis at that time. This incident has been a shift in Terry White's mission, which was the desired means of releasing the hostages in Lebanon, so that he himself would be a new hostage searching for someone to free him from kidnapping. The crisis increasingly deepened further as he lost the kidnappers' trust and their suspicions increased about his relationship with the CIA. White's name was also linked to suspicious arms deals that misled his mission in Lebanon. Therefore, this incident was a realistic embodiment of the contradiction prevailing in that era, which was full of conflicts and wars. White's time in captivity had a significant impact on important political transformations, which were reflected in the hostage release negotiations in general, and Terry White in particular.
Keywords: Terry Waite, Kidnapping, Anglican Church, Hostages